A Flipped Classroom Approach to Improve Nursing Students’ Learning Performance, Critical Thinking Skills, and Learning Satisfaction in a Stroke Care Training Course - hu, xiaoli; Zhao, Qian (Pacific International Journal, 2022)
The present study explored the effectiveness of presenting a stroke accident training program in three one-hour classes using a flipped classroom approach to traditional classroom teaching to third-year nursing students during their neurological clinical rotation. A quasi-experimental pretest and post-test study is designed to test the flipped classroom's effectiveness in improving learning outcomes. In so doing, eighty diploma nursing and midwifery students in the third-year clinical nursing program were selected from a medical college as the study participants. They were randomly assigned as the control and experimental groups, with 40 and 40 students. During the one-month training program, the control group (the non-flipped classroom) was taught using the traditional teaching method. In contrast, the experimental group (the flipped classroom) was taught in a flipped learning mode. The flipped sessions comprised pre-recorded lectures, online quizzes, and in-class group activities in the course design. Data were collected through a student questionnaire and a knowledge and skill test. Overall, the flipped classroom students did significantly better in learning performance (knowledge and skills), critical thinking and reported higher learning satisfaction (p<0.05). It was concluded that flipped classrooms can positively impact multiple factors within the clinical setting. Being better prepared will help newly graduated nurses care for not just stroke patients but for all patients requiring complex care.